3-(1H,1H,2H,2H-Perfluorooctyl)-1-vinyl-4-imidazoline-2-thione - Gabriel Partl; Gerhard Laus; Thomas Gelbrich; Klaus Wurst; Hubert Huppertz; Herwig Schottenberger (IUCrData, 2017)
The title compound, C13H9F13N2S, was obtained by reaction of sulfur with the corresponding quaternary salt in the presence of K2CO3. The quaternary salt in turn was obtained by alkylation of 1-vinylimidazole. The crystal structure contains two independent molecules with disordered fluoroalkyl chains with occupancy ratios of 0.7:0.3 and 0.57:0.43.